2017
DOI: 10.1188/17.onf.703-711
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress, Health Behaviors, and Benefit Finding in Survivors of Multiple Primary Cancers: Results From the 2010 Livestrong Survey

Abstract: Targeted distress screening in MPC survivors may allow for early identification and interventions to ameliorate distress and reduce negative downstream health effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…Self‐management is increasingly important as cancer care shifts to chronic disease management, and the responsibility of day‐to‐day management shifts from providers to patients and their families. Previous MPC literature supports the importance of self‐management, as survivors with MPC diagnoses have prolonged QOL deficits and view cancer as a chronic illness . Self‐management behaviors are teachable and modifiable and have the potential to improve health.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Self‐management is increasingly important as cancer care shifts to chronic disease management, and the responsibility of day‐to‐day management shifts from providers to patients and their families. Previous MPC literature supports the importance of self‐management, as survivors with MPC diagnoses have prolonged QOL deficits and view cancer as a chronic illness . Self‐management behaviors are teachable and modifiable and have the potential to improve health.…”
Section: Discussionmentioning
confidence: 98%
“…Diagnoses, treatment, and changes in the disease trajectory result in distress for patients with cancer and occur repeatedly in MPC . Our work, including a review of MPC literature, has identified MPC as a risk factor for psychological distress. The identified path between distress and functional health was not surprising, given the body of literature that has emerged from Lazarus and Folkman's early conceptualization of perceived stress .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some differences did exist between our sample and other published reports. First, as a result of our inclusion criteria, this sample of patients was, on average, closer to their first cancer diagnosis (M= 5.8 years, SD=2.9) than other published samples (11-17 years), providing the opportunity to examine a new cohort of MPC survivors not previously included in this body of literature (Belcher, Low, Posluszny, Kramer, & Donovan, 2016;. This study also included cancer sites not frequently represented in MPC literature (i.e., lung and thyroid cancer).…”
Section: Conclusion Implications For Nursing Future Studiesmentioning
confidence: 99%